Peran Kepala Desa dalam Pemilihan Kepala Daerah Kabupaten Deli Serdang Tahun 2018 - Lubis, Anita; Nasution, Muhammad Arif; Kusmanto, Heri (JPPUMA Jurnal Ilmu Pemerintahan dan Sosial Politik Universitas Medan Area, 2019)
The village is the smallest area in the Indonesian government structure that currently has a significant role and function in every social activity, both in the political, social, economic and legal contexts. The purpose of this study is to explain how the role of the village head and village apparatus in the implementation of regional head elections. This research uses a qualitative method with case studies. Data were obtained through in-depth interviews with village heads, village officials, community leaders, and also through literature studies. This study draws the conclusion that the role of the village head is very important in the implementation of regional head elections, particularly in relation to increasing the number of participation and managing potential conflicts in the community in the contestation of the campaign by the campaign team even though the election was carried out by only one pair of candidates against the empty box. The campaign will still be carried out by the winning team of candidates, at the same time the process of socialization and the program to increase voter turnout will also continue to be carried out by village officials in collaboration with election commision.